Transition-metal free C–C bond cleavage/borylation of cycloketone oxime esters. Issue 1 (10th October 2018) - Zhang, Jin-Jiang; Duan, Xin-Hua; Wu, Yong; Yang, Jun-Cheng; Guo, Li-Na
Abstract : An efficient transition-metal free C–C bond cleavage/borylation of cycloketone oxime esters has been described. In this reaction, the B2 (OH)4 reagent not only served as the boron source but also acted as an electron donor source through formation of a complex with a DMAc-like Lewis base. Abstract : An efficient transition-metal free C–C bond cleavage/borylation of cycloketone oxime esters has been described. In this reaction, the B2 (OH)4 reagent not only served as the boron source but also acted as an electron donor source through formation of a complex with a DMAc-like Lewis base. This complex could be used as an efficient single electron reductant in other ring-opening transformations of cycloketone oxime esters. Free-radical trapping, radical-clock, and DFT calculations all suggest a radical pathway for this transformation.